EARNING MANAGEMENT AND DETERMINANT FACTORS OF SOCIAL DISCLOSURE IN INDONESIAN COMPANIES - Sri Pujiningsih (Universitas Negeri Malang, 2015)
The objective of this study is to investigate relationship between earning management and factors, which determine social disclosure in Indonesia companies. Sample of this study are public companies that report social disclosure in annual report on period 2003–2006. Earning management measurement used Jones’s Model. Whereas, regression analysis is used to explain relationship social disclosure index as dependent variables and independent variables, that consist of earning management, managerial ownership, leverage, size, board of commisioners and profitabilty. The results of this study show that public companies in Indonesia, that have disclosed social activities in annual report, conduct earning management. Beside this, the result of this study find significant relationship between size with social diclosure. In the other hand, there is no realtionship between profitability, managerial ownership, leverage, board of commissioners and earning management with social disclosure.Keywords: earning management, social disclosure, agency theory, stakeholder theory, legitimacy theory